(a-5)=36

Simple and best practice solution for (a-5)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (a-5)=36 equation:


Simplifying
(a + -5) = 36

Reorder the terms:
(-5 + a) = 36

Remove parenthesis around (-5 + a)
-5 + a = 36

Solving
-5 + a = 36

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + a = 36 + 5

Combine like terms: -5 + 5 = 0
0 + a = 36 + 5
a = 36 + 5

Combine like terms: 36 + 5 = 41
a = 41

Simplifying
a = 41

See similar equations:

| 10v^2-27v+5=0 | | -a/5=1/5 | | (x+3)(x+1)=4x+7 | | 2x^2+4x=621 | | t^2+4t+4=7 | | -5k=-14 | | 8x+3=4x+3 | | (u+1)*10=40 | | (q-10)*5=50 | | 5+3r=5 | | 2-2x/5=x-6 | | x^2+6x=120 | | 7x+3=19+5x | | 8y-2=14y-4 | | b=1/3=2 | | X^2+6x+33=0 | | (-4e^-2x)/(e^-5x) | | 16-3x=-7x+12 | | 5a^2-21a+18=0 | | 2/3a^2=23 | | 6x-10=-20 | | 14fa-72a^2+f^2= | | 2/3g=6=-12 | | -5z+6=6z-38 | | 144=-12(X+-60) | | a*bcd=bcd*a | | 1X+8=3X+14 | | (x+y)=3(x+y)-2 | | 4x-(3x-7)-(2x-3)=8x(x-1) | | 8z+4=11z-17 | | 3x+4(1)=-2 | | 5(2u-2)-12u= |

Equations solver categories